Sex differences in young gymnasts' postural steadiness - Milosis, D. C.; Siatras, T. A. (Perceptual and Motor Skills, 2012)
The present study examined the differences between male and female gymnasts in bipedal standing position, back standing scale, and stork standing scale testing. 29 young gymnasts (13 boys, 16 girls; ages 12 to 15 years) participated. A portable posturographic digital platform was used to record foot pressure (Foot Checker, Comex SA). Barefoot sole area (cm²), maximal pressure (kPa), center of foot pressure (CoP), sway area (mm²), and CoP linear distance displacement (mm) were analyzed in an integrated software module (Foot Checker, Version 4.0). The intra-class correlation coefficient and the coefficient of variation supported the reliability of the measurements. Results indicated no differences between boys and girls on height, weight, and Body Mass Index. Differences indicated better performance by girls compared to boys in back standing and stork standing.